Stage-structured lefkovitch matrix population modelling aedes aegypti / Marina Mahajid, Nur Adriana Azween Ahmad Sanizam and Nur Syahida Dzulfukar - Mahajid, Marina; Ahmad Sanizam, Nur Adriana Azween; Dzulfukar, Nur Syahida (2019)
Aedes aegypti is the prime factor of dengue virus which dynamic of its population can be influenced by the fluctuation of rainfall. The purpose of conducting this project is mainly to simulate the mosquito population growth associated with rainfall distribution. The dynamic of the mosquito population was simulated by using the transition matrix which is Lefkovitch matrix model. The life cycle ofAedes aegypfi consists of five stages which are eggs, larva, pupae, adult l and adult 2. These five stages of the mosquito life cycle were used in constructing the transition matrix for the matrix model. The study of this report was focused in Shah Alam, Selangor since it has the highest number of reported dengue cases in Malaysia. Therefore, the data of daily rainfall distributions in Subang has been used in this study. The findings of this project show that the population of Aedes aegypli will be influenced by the rainfall distribution. The growth of Aedes aegypti will be affected when there is no rain or heavy rain. This is because this situation could hinder the fertilization of eggs or affect their breeding habitats. Therefore, the researchers need to further studies on survival and hatching rate based on the current environment, so that the prediction will be more accurate and get more knowledge on the population of Aedes aegypti.